PROGRAM BIMBINGAN DENGAN TEKNIK ROLE PLAYING UNTUK MENGEMBANGKAN ORIENTASI KARIR SISWA (Jurnal Bimbingan dan Konseling Islam, 2016)
This study exposed behind by the importance of career orientation in the lives of teenagers in the age of  junior hight school. The study aimed effectiveness of guidance by role playing techniques to develop students' career orientation. This study is based on the theory of career maturity by Donald E. Super which focuses on the career development process focuses on the growth and direction of individual career issues throughout its life span. This study uses a quantitative approach, the experimental method and design repeated measures design. The study was conducted at the Junior School Master of Indonesia, Depok (school orphans and street children) by the number of participants as much as 7 student experiments. The sampling technique used was purposive sampling. Data on career orientation were collected using a questionnaire developed career orientation of the theory of Donald. E. Super. Data analysis technique used was Wilcoxon test. The results showed an increase in student scores experimentation before and after the intervention as well as changes in the behavior of each counseling session. Recommendations of the research  was intended to: (1) Master of Guidance and Counseling should be active and creative in using the techniques in providing guidance and counseling services. (2) School Master Indonesia which practically should undertake the preparation of additional learning activities with role playing techniques as an alternative to the teaching at the school in directing students to plan their future. (3) Homes to provide child protection services with role playing as an alternative technique to provide a good lesson to plan for the future and the needs of others. (4) Researchers further to follow up the results of the study with regard variables related career orientation.